C4 Photosynthesis in the Rice Paddy: Insights from the Noxious Weed Echinochloa glabrescens. Issue 1 (2nd November 2015) - Covshoff, Sarah; Szecowka, Marek; Hughes, Thomas E.; Smith-Unna, Richard; Kelly, Steven; Bailey, Karen J.; Sage, Tammy L.; Pachebat, Justin A.; Leegood, Richard; Hibberd, Julian M.
Abstract : Transcriptomic profiling of the paddy weed Echinochloa glabrescens identifies its C4 molecular signature and genes important for paddy growth. Abstract: The C4 pathway is a highly complex trait that increases photosynthetic efficiency in more than 60 plant lineages. Although the majority of C4 plants occupy disturbed, arid, and nutrient-poor habitats, some grow in high-nutrient, waterlogged conditions. One such example is Echinochloa glabrescens, which is an aggressive weed of rice paddies. We generated comprehensive transcriptome datasets for C4 E. glabrescens and C3 rice to identify genes associated with adaption to waterlogged, nutrient-replete conditions, but also used the data to better understand how C4 photosynthesis operates in these conditions. Leaves of E. glabrescens exhibited classical Kranz anatomy with lightly lobed mesophyll cells having low chloroplast coverage. As with rice and other hygrophytic C3 species, leaves of E. glabrescens accumulated a chloroplastic phospho enol pyruvate carboxylase protein, albeit at reduced amounts relative to rice. The arid-grown species Setaria italica (C4 ) and Brachypodium distachyon (C3 ) were also found to accumulate chloroplastic phospho enol pyruvate carboxylase. We identified a molecular signature associated with C4 photosynthesis in nutrient-replete, waterlogged conditions that is highly similar to those previously reported from C4 plants that grow in more arid conditions. We also identified a cohort of genes that have been subjected to a selective sweep associated with growth in paddy conditions. Overall, this approach highlights the value of using wild species such as weeds to identify adaptions to specific conditions associated with high-yielding crops in agriculture.